DEVELOPMENT OF INTERACTIVE LEARNING MEDIA BASED ON QUIZIZZ GAMES - Pakudu, Radit; Rizal; Safaat, Mohamad (Jurnal Ilmu Pendidikan dan Budaya, 2024)
The platform plays a key role in creating an inclusive and engaging learning experience for students with diverse learning styles. Through interactive quizzes tailored to your needs, Quizizz enables wider accessibility to learning material. With the ability to provide immediate feedback, teachers can track individual student progress, identify gaps in understanding, and provide needed personalized assistance. By presenting educational content in an interesting game format, Quizizz is able to arouse students' interest in learning more actively. This research aims to develop interactive learning media based on the Quizizz game using the ADDIE model. In the implementation stage, the product is not tested directly on students, but goes through an evaluation and validation stage. Product validation is carried out to ensure that the learning media meets the specified success criteria, making the product ready to be implemented without involving direct trials on students. This research contributes to designing and developing interactive learning media that suits learning needs, with a focus on product validation as an indicator of quality and effectiveness. The use of the Quizizz game as an interactive learning medium provides opportunities for students to learn independently, while remaining actively involved in the learning process. Thus, the implementation of the ADDIE model in the development of Quizizz-based interactive learning media opens the door to creating more enjoyable, effective and measurable learning for students.